Efecto de las dosis y frecuencias de aplicación de Azotobacter sobre el crecimiento y producción del cultivo de maíz en el cantón Bolívar - Solórzano Valencia, Diego Francisco (2025)
The present experimental research aimed to compare the effect of different doses and application frequencies of the biofertilizer Azotobacter on growth and production variables of maize (Zea mays L.) in the Bolívar canton. Treatments combined three levels of Azotobacter doses (1, 2, and 3 L ha⁻¹) with and without chemical fertilization (275 kg ha⁻¹ of NPK), applied either once or twice during the crop’s phenological cycle. The results showed that the application of Azotobacter with chemical fertilization significantly increased crop yield, with the dose of 2 L ha⁻¹ + 275 kg ha⁻¹ of NPK (D4) presenting the highest agronomic efficiency. On the other hand, applying the treatments at two phenological stages optimized the morphological and productive components of the crop compared to a single application. The biofertilizer acted as a biological nitrogen fixer, complementing chemical fertilization and improving grain yield. The economic analysis revealed that treatments T8 (2 L ha⁻¹ + 275 kg ha⁻¹ of NPK, with two applications), T7 (2 L ha⁻¹ + 275 kg ha⁻¹ of NPK, with one application), and T6 (3 L ha⁻¹, with two applications) were the most profitable, achieving benefit margins between 82% and 92% higher than the control. It is concluded that the use of Azotobacter at optimal doses and frequencies constitutes an effective agro-biotechnological strategy to improve maize yield and profitability under local conditions.